Clinical, radiological and pathological findings of primary nasal osteosarcoma in a Libyan cat - Mohamed H. Abushhiwa; Seham A. Al-Azreg; Samer K. Tmumen; Abdulrhman M. Alrtib; Abdulkareem K. Elbaz; Mahir A. Kubba; Al-Asayed R. Al-Attar; Emad M. Bennour (Open Veterinary Journal, 2019)
Background: Although bone tumors are common pathologies in companion animals, limited reports describe nasal osteosarcoma (OSA) in cats. Case Description: A case of nasal OSA in a local Libyan cat was admitted to the Veterinary Teaching Hospital at the Faculty of Veterinary Medicine at the University of Tripoli – Libya, with nasal swelling and discharges and facial deformity. The radiological findings revealed nasal osteolysis with absence of evidence of lung metastasis. In addition, fungal growth was not identified on microbiological culture. Furthermore, the pathological examination has grossly revealed a destructed nasal bone due to the presence of a tumor mass, with a muco-hemorrhagic nasal discharge and absence of metastasis. OSA was confirmed histopathologically. Conclusion: This report presents the clinical, radiological and pathological findings of a primary nasal OSA in a Libyan cat with no tumor metastasis to other body organs.